The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1055/a-1008-6138
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Protective Effects of Centella asiatica and Its Triterpenes: A Review

Abstract: Centella asiatica, a triterpene-rich medicinal herb, is traditionally used to treat various types of diseases including neurological, dermatological, and metabolic diseases. A few articles have previously reviewed a broad range of pharmacological activities of C. asiatica, but none of these reviews focuses on the use of C. asiatica in cardiovascular diseases. This review aims to summarize recent findings on protective effects of C. asiatica and its active constituents (asiatic acid, asiaticoside, madecassic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 95 publications
0
34
0
Order By: Relevance
“…As a triterpene-rich medicinal Chinese traditional herb, Centella asiatica has been extensively demonstrated to have therapeutic value in various types of diseases, including neurological, dermatological, and metabolic diseases [ 28 ]. Centella asiatica- derived molecules have been widely documented to treat multiple types of cancer [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a triterpene-rich medicinal Chinese traditional herb, Centella asiatica has been extensively demonstrated to have therapeutic value in various types of diseases, including neurological, dermatological, and metabolic diseases [ 28 ]. Centella asiatica- derived molecules have been widely documented to treat multiple types of cancer [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…anti-alzheimer and anti-depressant 8,9,64 . Scientific studies showed numerous pharmacological activities of CA, including memory enhancing and learning, neuroprotective, anxiolytic, antiinflammatory, wound healing, cardiovascular protective and anti-cancer, thereby validating its traditional claims 7,10,11,56,63 . The plant contains various phytoconstituents viz.…”
Section: Introductionmentioning
confidence: 88%
“…The aglycone asiatic acid was found to exert a promising effect on SK-MEL-2 human melanoma cells with IC 50 = 40 µM, due to the antiproliferative activity and induction of cell cycle arrest. In addition, asiatic acid has been also correlated to the cardiovascular protective effect of C. asiatica [14]. Madecassoside (2) and madecassic acid have shown anti-inflammatory activity since they can inhibit the production of lipopolysaccharide (LPS)-induced nitric oxide (NO) and prostaglandin E 2 (PGE 2 ) [15].…”
Section: Introductionmentioning
confidence: 99%